2021
DOI: 10.3390/biomedicines9121825
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Carbon Dioxide Decellularized Bone Matrix Seeded with Adipose-Derived Mesenchymal Stem Cells Accelerated Bone Regeneration

Abstract: Large bone fractures with segmental defects are a vital phase to accelerate bone integration. The present study examined the role of supercritical carbon dioxide (scCO2) decellularized bone matrix (scDBM) seeded with allogeneic adipose-derived mesenchymal stem cells (ADSC) as bio-scaffold for bone regeneration. Bio-scaffold produced by seeding ADSC to scDBM was evaluated by scanning electron microscopy (SEM). Rat segmental femoral defect model was used as a non-union model to investigate the callus formation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…It is shown that PCL scaffolds with the transient release of hyperoxia enhance ASC-mediated skull regeneration in mice ( Farris et al, 2022 ). These findings provided biological clues for the application of scaffolds ( Liu et al, 2021 ). Nanomaterials have made new progress in ASCs contributing to bone formation.…”
Section: Distinct Animal Models Of Ascs Contributing To Bone Repair H...mentioning
confidence: 84%
See 1 more Smart Citation
“…It is shown that PCL scaffolds with the transient release of hyperoxia enhance ASC-mediated skull regeneration in mice ( Farris et al, 2022 ). These findings provided biological clues for the application of scaffolds ( Liu et al, 2021 ). Nanomaterials have made new progress in ASCs contributing to bone formation.…”
Section: Distinct Animal Models Of Ascs Contributing To Bone Repair H...mentioning
confidence: 84%
“…Another animal experiment showed that the combination of ASCs improved the gap and surrounding ossification of the scaffold compared with the scaffold alone ( Lee et al, 2021 ). ASCs also display the ability to accelerate bone formation after using biological scaffolds ( Liu et al, 2021 ).…”
Section: Various Ways To Promote Asc Osteogenesis At the Cellular Levelmentioning
confidence: 99%
“…Although using in vivo and in vitro bioreactors can improve the adhesion coefficient and differentiation of cells loaded on ABGs, indicators such as cell migration or leaching, dedifferentiation, and apoptosis of stem cells in therapeutic processes simply affect treatment efficacy. In this regard, Liu et al 136 based on the SEM results showed that fat stem cells loaded on ABGs derived from porcine bone through physical approach (supercritical carbon dioxide with a pressure of 350 bar at 45 °C for 80 min) were effectively placed on the cavities. However, the regeneration time ranged between 12 and 24 weeks, indicating a delay in biological functions of such as cell migration, adhesion, and differentiation to osteogenic cells in vivo.…”
Section: Xenogeneic Abgsmentioning
confidence: 99%
“…Despite an increase in bone mass and upregulation of K i -67, BMP-2, and OCN mRNA, which indicate promising cell differentiation, the slow rate of bone repair by ABGs can pose a challenge to therapeutic efficacy, particularly in diabetic, osteoporosis, and infectious disease patients. 136 Other agents, such as drugs or nanomaterials, appear to be effective in stimulating rapid proliferation and differentiation of stem cells in ABGs. For instance, Parmaksiz et al 137 by integrating 12−18 nm iron nanoparticles in the production process of ABGs molded from bovine tibia head granules using a chemical-enzymatic approach showed that the healing rate of rat calvaria bone tissue increases through osteoinductive amplification by low frequency-pulsed electromagnetic field.…”
Section: Xenogeneic Abgsmentioning
confidence: 99%
“…Implantation of the DPB seeded ASCs stimulated endochondral ossification for substantial bone regeneration. The DPB seeded ASCs system is of clinical relevance for segmental defect bone regeneration [40].…”
Section: Bonementioning
confidence: 99%